Зачеловек: [фантастический роман] : цикл "Трое из леса" / Юрий Никитин - Никитин Юрий Александрович (Эксмо, 2004)
Экземпляры: ООВ (20160318) / Инвентарный номер: 39089 / Цена: 39.00 / Авт.знак: Н 62 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6